Leaflets three, let it be! : the story of poison ivy - Sanchez, Anita, 1956- (Boyds Mills Press, an imprint of Highlights, 2014)
Looking past its itch-inducing nature, describes the other things that poison ivy can do, from providing food for rabbits in spring to being used as shade by salamanders in the summer.